Gereja dan Adat: Kasus Gondang Sabangunan dan Tortor - Mauly Purba (Antropologi Indonesia, 2000)
From the 1860's up to the 1940's, German missionaries under the leadership of Dr. I.L.Nommensen succeeded in converting many of the Batak Toba to Christianity, and along with the Dutch colonial government developed a Western education system in the Batak homeland. Following this, educational improvement among the Batak Toba helped foster the development of Christianity and the Church. As a further development, the Church has extended its reach from matters of personal life to the collective life of the Batak Toba. While introducing new values to the people, the Church seeks to eradicate traditional cultural values that are not in accord with its own, such as the gondang sabangunan and tortor (the ceremonial music and dance of the Batak Toba) and a number of ritual ceremonies. The Church's desire is today reflected in the book Hukum Siasat Gereja, which deals with the norms of Christian social life. Several articles in the book place restrict the musical activity of Christian Batak Toba, especially the performance of gondang sabangunan and tortor in the context of ritual ceremonies. Through an ethno historical approach, this article examines change in the functions and dynamics of gondang sabangunan and tortor performances among the Christian Batak Toba of North Sumatera. The study covers the period between the 1860's and the 1990's. Aside from discussing a number of social and cultural factors that have led to changes in the function of the ceremonial music and dance, several rulings on the performance of gondang sabangunan and tortor in the Hukum Siasat Gereja will also be discussed. The purpose of this last discussion is to show the extend of the Church's influence in the context of this change. The article also provides a discussion on the response of the Christian Batak Toba toward these rulings.